Vinyl moon - Browne, Mahogany L. (Crown Books for Young Readers, 2022)
"A teen girl hiding the scars of a past relationship finds home and healing in the words of strong Black writers. A beautiful sophomore novel from a critically acclaimed author and poet that explores how words have the power to shape and uplift our world even in the midst of pain. When Darius told Angel he loved her, she believed him. But five weeks after the incident, Angel finds herself in Brooklyn, far from her family, from him, and from the California life she has known. Angel feels out of sync with her new neighborhood. At school, she can't shake the feeling everyone knows what happened--and that it was her fault. The only place that makes sense is Ms. G's class. There, Angel's classmates share their own stories of pain, joy, and fortitude. And as Angel becomes immersed in her revolutionary literature course, the words from novels like The Bluest Eye and Push speak to her and begin to heal the wounds of her past. This stunning novel weaves together prose, poems, and vignettes to tell the story of Angel, a young woman whose past was shaped by domestic violence but whose love of language and music and the gift of community grant her the chance to find herself again."--